A short-lived fish with long-lasting effects: hallmarks of aging in Nothobranchius furzeri - Savel, Oksana; Lehmann, Julien; Poyraz, Yusuf Kaan; Page, Melissa Marie (Frontiers in Aging, 2026)
Our world is facing a global aging crisis with an increasing number of people living longer in poor health, as indicated by a gap between lifespan and healthspan. It is necessary to improve our knowledge of the biomolecular and cellular pathways implicated in aging to improve the overall healthspan of the population and lift the economic and social burden of age-related diseases. Gerontologists have defined twelve hallmarks of aging to study them efficiently. Here we review each aging hallmark in the context of N. furzeri, a short-lived model fish. Introduced to the lab in 2003, this fish has the shortest vertebrate lifespan recorded in captivity. Depending on the strain, it lives between 2 months to 1 year. While aging, it develops several age-related phenotypes experienced by humans, such as emaciation, spine curvature, locomotor and cognitive defects. We summarize that aged Nothobranchius furzeri develop characteristics of each hallmark with high similarity to humans and other aging models. For several of these hallmarks, interventions that accelerate aging clearly leads to reduced health and a shorter lifespan, expanding our knowledge on molecular mechanisms favoring shorter healthspan. Interventions that decelerate aging have demonstrated a positive impact on health or an extension to lifespan, that could be transferred to humans for an increased healthspan. For example, the link between glucose metabolism and ER stress or the use of young microbial gut transplant to improve health are two discoveries made in N. furzeri and are of relevant importance for human healthy aging. By comparing similar ages and strains and by using standardized breeding procedures, the N. furzeri community will continue to greatly contribute to aging research. Creating stable transgenic lines and finding a way to administer drugs efficiently are two challenges that must be addressed to test novel targets of interests or therapies in each hallmark of aging.